Validity of an Alternate Hand Behind Back Shoulder Range of Motion Measurement in Patients With Shoulder Pain and Movement Dysfunction - Satpute, K.; Hall, Toby; Adanani, A. (Elsevier Inc, 2018)
Objectives: The purpose of this study was to determine the criterion-related validity of a novel method of measuring hand behind back (HBB) shoulder range of motion (ROM) for evaluating pain and disability in people with shoulder pain and movement impairment. Methods: This cross-sectional study design evaluated shoulder ROM, pain, fear-avoidance beliefs, and disability in 60 people (aged 35-70 years, 31 male) with chronic unilateral shoulder dysfunction (mean duration 15.73 weeks). Shoulder HBB ROM was measured with a bubble inclinometer in a manner that did not require the patient to disrobe. Correlations were sought between HBB ROM and other shoulder movements, as well as scores recorded on the Shoulder Pain and Disability Index (SPADI), visual analogue scale for pain, Fear Avoidance Beliefs Questionnaire (FABQ), and duration of symptoms. Results: Restriction of HBB movement was significantly correlated with SPADI total disability score (r = 0.39, P < .01), flexion ROM (r = 0.30, P < .05), abduction ROM (r = 0.39, P < .01), and external rotation ROM (r = 0.60, P < .01). Other variables were not significantly correlated with HBB ROM. Multiple linear regression analysis indicated that the variance in HBB ROM was explained by the SPADI disability subscore (P =.01) but not by visual analogue scale score (P =.05), FABQ score (P =.65), or duration of symptoms (P =.73). The FABQ score was not explained by limitation in HBB ROM and shoulder movements. Conclusion: These findings suggest that this novel method of measuring HBB ROM could be used as a functional outcome measure in the evaluation of patients with shoulder disorders. This method could be considered as an additional or alternative where there are challenges in measuring HBB because of restrictions in undressing a patient, such as for cultural reasons.